Perbandingan Penggunaan Daya Listrik Antara Baremetal Dengan Docker Container Pada Raspberry Pi 4B - Hasvid Dwi Putranto; Muhammad Koprawi, S.Kom., M.Eng. (AI Society & STMIK Indonesia, 2024)
In today's development, many services are starting to use Container base services where it is easier to do development and there is also a lot of implementation documentation. But there are also those who still use Baremetal where installing the service is installed directly on the Operating System (OS) and some people are used to using Baremetal in this case the application on the Edge Server or Internet of Things (IoT) such as on the Raspberry Pi, electricity usage is a limitation in making an efficient system so that in this study, will compare electricity usage in Input/output operations per second (IOPS) and Floating point operations per second (Flops). And the results show that Baremetal's electricity usage is smaller than that of Docker Container where the difference is 1.06 GigaFlops/Watt on HPLinpack and on IOPS/Watt, Baremetal is far superior to Docker Container where in IOPS read/Watt superior to 3246.12 and in IOPS write/Watt superior to 1857.51 it is because Docker Container uses several services to run its Container so that it consumes more power.